Caste, race and discrimination discourses in international context - Thorat, Sukhadeo (Indian Inst. of Dalit Studies, 2004)
Contributed articles on caste, Dalits, and racial discrimination against them.
Includes index - Includes bibliographical references
Keywords: Caste -- India; Caste-based discrimination -- India; Dalits -- India; Race discrimination -- India; Kaste; Diskriminierung; Indien; India -- Race relations; Aufsatzsammlung